Home, yard and neighbourhood: Women's work and the urban working-class family economy, Ottawa, 1871. - McLean, Lorna Ruth. (University of Ottawa (Canada), 1990)
This thesis examines the work of married women in working-class families in Ottawa in 1871. It demonstrates that home production by women for consumption, sale and/or exchange, together with arrangements of household structures, made a primary and fundamental contribution to the survival of the family unit. Women laboured and their labour was vital. Using the 1871 manuscript census, the study analysed the myriad of ways that married women utilized their available resources to reduce expenditures and to increase the wage-based family income. It was the work of women that provided some protection against the insecurity of inadequate wages, seasonal employment, illness or death.
Keywords: History, Canadian.